A 512-mb DDR3 SDRAM prototype with CIO minimization and self-calibration techniques. - Churoo Park (IEEE Journal of solid state circuits)
A 1.5-V 512-Mb DDR3 synchronous DRAM prototype was designed and fabricated in 80-nm technology. Critical to the signal integrity in DDR3 point-to-2points (P22P) interfacing is an efficient calibration scheme and CIO minimization, which were achieved by on-die-termination (ODT)-merged output drivers, SCR type ESD protection, and self-calibration scheme. The hybrid latency control scheme can turn the DLL off in standby mode, reducing power consumption. User-friendly functions such as temperature read-out from on-chip sensor and per-bank-refresh were also implemented.